Adsorption of Iron by Fly Ash Adsorbent of Coal - Irawan, Candra; Atikah, Atikah; Rumhayati, Barlah (Chemistry Department, The University of Brawijaya, 2014)
This research has investigated adsorption of Fe with using fly ash adsorbent. Phases of adsorption of Fe isactivatedwithH2SO4afterthat thefly ashwere characterizedby usingXRF, FTIRandSEM. Determination ofoptimum conditionsonthe adsorptionof Fewithadsorbentmassvariations, variations incontact time, pHvariationandvariationconcentration andadsorptionisothermstudy. Resulth showthat theadsorptionof Fein optimum conditionoccurs inadsorbentmass of2.5g, for 60minutescontact timewithpH4at a concentration of20ppm. The results alsoable toadsorpup to94% Fe. The adsorption of Fe with using fly ashadsorbentwas more fitted to theLangmuirmodel than to Freundlich model <w:LsdException Locked=